RUMAH IBADAH SEBAGAI MEDAN KONTESTASI BERAGAMA - Saprillah Saprillah (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2017)
The house of worship become an interesting phenomena among the religion community, in recent years. The minority tends very hard to build their houses of worship. This paper aims to describe that houses of worship become battle area among the reliogion community. Seven cases of houses of worship in East Kalimantan are best example for that symbolic battle. Not only between two different religion community but also the same religion community.This paper explains that houses of worship become battle area among the reliogion community was caused by; 1) houses of worship is well known as symbolic and artificial. Not just for pure worship for sure. 2). Syndrome of majority. The majority reject to live side by side in peace. 3). Those people are not ready to live together in multicultural area.